EFFECTS OF HEALTH LITERACY PROGRAM FOR DIABETES MELLITUS PREVENTION AMONG RISK GROUPS OF DONGDINDANG SUB-DISTRICT HEALTH PROMOTING HOSPITAL NONG MUANG DISTRICT, LOPBURI PROVINCE - อวิชัย, ปัทมพร; หีบแก้ว ปัดชาสุวรรณ์, นาฏนภา; คาวีวงศ์, ดุษฎี; ตัญตรัยรัตน์, พฤกษ์ (Primary Health Care Journal (Northeastern Edition), 2026)
This quasi-experimental research aimed to determine the effects of a health literacy program for prevention of diabetes at-risk individuals. The sample consisted of 72 participants at risk for diabetes, equally divided into an experimental group (n = 36) and a comparison group (n = 36). The experimental group participated in a 10-week health literacy program. Data were collected using health literacy and health behavior assessment tools and analyzed using paired t-test and independent t-test. The results revealed that after the intervention, the experimental group demonstrated significantly higher mean scores in accessing, understanding, evaluating, and applying health information, as well as in self-care behaviors, compared to both their baseline and the comparison group (p-value < 0.001). Furthermore, the experimental group's mean blood sugar level significantly decreased compared to the baseline (Mean diff. = 27.83, 95% CI: 25.73 to 29.93, p-value < 0.001) and was significantly lower than that of the comparison group (Mean diff. = 18.72, 95% CI: 12.43 to 25.01, p-value < 0.001). In conclusion, this health literacy program effectively enhanced health literacy levels and promoted self-care behavior modifications among the at-risk group, leading to a successful reduction in blood sugar levels. It is recommended that relevant agencies implement this program for diabetes risk groups in other areas with similar contexts.